Efektivitas penggunaan model pembelajaran kooperatif tipe STAD berbantuan media ajar jaring-jaring bangun ruang terhadap hasil belajar matematika (studi siswa kelas V SDN 6 Watampone) - Firdaus; Kadir, Abd; Ardani, Maulidya (MACCA : Science-Edu Journal, 2026)
This study employed a quantitative experimental approach using a One Group Pretest–Posttest Design to determine students’ mathematics learning outcomes before and after the implementation of the STAD-type cooperative learning model assisted by three-dimensional shape nets media. The population consisted of all fifth-grade students of SDN 6 Watampone, with a sample of 24 students selected through saturated sampling. Data were collected using tests to measure students’ mathematics learning outcomes before and after the treatment, questionnaires to assess students’ responses toward the learning model, and observation sheets to evaluate the implementation of the learning process. Data were analyzed using descriptive and inferential statistics. The descriptive analysis showed that the mean Pretest score was 55.55, while the mean Posttest score increased to 72.50. The average score of students’ responses was 86.95, indicating a very positive response, and the average implementation score was 92.59. The prerequisite tests showed that the data were normally distributed and homogeneous. The paired samples t-test revealed a significance value of 0.001 < 0.05, indicating a significant difference between students’ mathematics learning outcomes before and after the implementation of the STAD-type cooperative learning model assisted by three-dimensional shape nets media. Therefore, the STAD-type cooperative learning model assisted by three-dimensional shape nets media is effective in improving fifth-grade students’ mathematics learning outcomes at SDN 6 Watampone.